2017
DOI: 10.1523/jneurosci.1453-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Gap Junction–Mediated Signaling from Motor Neurons Regulates Motor Generation in the Central Circuits of LarvalDrosophila

Abstract: In this study, we used the peristaltic crawling of Drosophila larvae as a model to study how motor patterns are regulated by central circuits. We built an experimental system that allows simultaneous application of optogenetics and calcium imaging to the isolated ventral nerve cord (VNC). We then investigated the effects of manipulating local activity of motor neurons (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 56 publications
5
23
0
Order By: Relevance
“…As described above, this would lead to a change in the firing frequency of VPN neurons and thus modify VMN activity. Similar motor–premotor coupling has recently been shown in zebrafish and Drosophila locomotor networks in regard to motor rhythm control (Matsunaga, Kohsaka, & Nose, ), as well as in the Xenopus vocal pattern generator (Lawton, Perry, Yamaguchi, & Zornik, ).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…As described above, this would lead to a change in the firing frequency of VPN neurons and thus modify VMN activity. Similar motor–premotor coupling has recently been shown in zebrafish and Drosophila locomotor networks in regard to motor rhythm control (Matsunaga, Kohsaka, & Nose, ), as well as in the Xenopus vocal pattern generator (Lawton, Perry, Yamaguchi, & Zornik, ).…”
Section: Discussionsupporting
confidence: 65%
“…Electrophysiological recordings from VPN in midshipman fish strengthen this hypothesis as current injection into VPN neurons does not induce the characteristic firing frequency displayed during vocal activity (Chagnaud et al, 2012). (Matsunaga, Kohsaka, & Nose, 2017), as well as in the Xenopus vocal pattern generator (Lawton, Perry, Yamaguchi, & Zornik, 2017).…”
Section: Gabamentioning
confidence: 88%
“…The intrinsic activity of the AS MNs correlates best with forward locomotion, which corresponds to a stronger response of AS MNs to photodepolarization of the forward PIN AVB. Functionally asymmetric electrical connections suggest AS MN feedback control of the backward PIN AVA, a feature recently observed for locomotor circuits also in other animals (Matsunaga et al, 2017; Song et al, 2016).…”
Section: Introductionsupporting
confidence: 59%
“…Despite anatomical prevalence of chemical synapses from AVA to AS MNs, our data showed larger AS MN effects after stimulation of the forward PIN AVB, and a stronger correlation of AS MN activity with forward locomotion. Recently, ability of MNs to modulate activity of PINs was shown in several animal models: for B-type MNs changing the inhibitory chemical transmission of AVB to AVA in C. elegans (Kawano et al, 2011; Liu et al, 2017); for MNs regulating the frequency of crawling in Drosophila (Matsunaga et al, 2017); for MNs affecting activity of the excitatory V2a neurons in zebrafish (Song et al, 2016); and, in the mouse, such activity was suggested for MNs, changing the frequency of rhythmic CPG activity after stimulation by rhodopsins (Falgairolle et al, 2017). Positive feedback from MNs required the function of gap junctions, coupling between MNs and PINs in all these systems.…”
Section: Discussionmentioning
confidence: 99%
“…This points to the possibility of a dedicated D1-dependent circuit that could underlie the generation of rhythmic activities elicited by high concentrations of dopamine. Motoneurons compose key rhythm generating elements in invertebrate circuits [66][67][68] and also participate in rhythm generation in vertebrates [69], including rodents [32,40,56,70,71]. V3 interneurons are one subclass of geneticallydefined spinal interneuron that are important for the generation of rhythmic activities in mammalian spinal networks [53,55,72] and receive recurrent excitatory collaterals from motoneurons in rodents [32].…”
Section: Dedicated Network Components Segregate Excitatory and Inhibimentioning
confidence: 99%